2016
DOI: 10.1245/s10434-016-5622-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Delayed Time to Adjuvant Chemotherapy and Disease-Specific Survival in Stage III Colon Cancer Patients

Abstract: These findings suggest there is substantial variation in time to adjuvant chemotherapy among stage III colon cancer patients. Reasons for delays may be due to system factors that influence individual providers to make varying decisions on the time of initiation. Future research should identify what these factors may be and how to address them to promote better delivery of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This left 34 studies with unique populations for inclusion ( fig 1 , table 1 , table 2 ). 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 These studies included 1 272 681 patients, with a sample size ranging from 174 to 420 792 (appendix 3). Twenty eight studies were population or registry based, and six were institutional reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This left 34 studies with unique populations for inclusion ( fig 1 , table 1 , table 2 ). 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 These studies included 1 272 681 patients, with a sample size ranging from 174 to 420 792 (appendix 3). Twenty eight studies were population or registry based, and six were institutional reports.…”
Section: Resultsmentioning
confidence: 99%
“… 1 2 3 47 We also note major detrimental effects of prolonged waiting times on cancer specific survival outcomes in 13 of 15 studies included in our meta-analysis that reported cancer survival outcomes alongside overall survival. 14 16 22 28 29 30 31 32 33 34 35 36 38 39 46 These studies span seven treatment indications. Factors associated with medical status such as elements of socioeconomic status or insurance status might also be confounding factors; we found that 91% and 82% of identified studies accounted for these, respectively, though this does not completely rule out the possibility of residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…These 34 studies corresponded to the post-hoc analyses of randomized controlled trials and cohorts and to retrospective studies. They included a total of 141,853 patients: 134,701 in the colon cancer cohort, as shown in Table 1 [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]; 5121 in the gastric cancer cohort, as shown in Table 2 [26,27,28,29,30,31]; and 2031 in the pancreatic cancer cohort, as shown in Table 3 [32,33,34,35,36,37]. Among these studies, 22 were used for the colorectal cancer analysis and six were used for pancreatic and gastric cancer each.…”
Section: Resultsmentioning
confidence: 99%
“…From an oncological perspective, to eliminate microscopic metastasis it appears that AC should be started immediately following curative gastrectomy. PDAC has been reported to be an independent prognostic factor in other types of cancer, with various cutoff values suggested, including 12 weeks [10] and 8 weeks in colon cancer [15][16][17] and 13 weeks (91 days) in breast cancer [18]. With regard to gastric cancer, various cut-off values of PDAC have been reported as prognostic factors, ranging from 4 to 8 weeks [12,16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%